BOX GAME AND DISPLAY BANNER UNTUK MELATIH KONSENTRASI, MOTORIK, DAN MELATIH BAHASA DAN WAWASAN - Maulidiyah, Ummi Masrufah; Dzulkifli, Dzulkifli; arumsari, andini dwi (MOTORIC, 2023)
Educational games are games that have educational elements that are obtained from something that exists and is attached and becomes part of the game itself. Educational Game Tools (APE) are everything that can be used as a means or equipment to play that contains educational value and can stimulate the growth of the child's brain to develop all aspects of the child's ability (potential). The purpose of educational game tools in the learning process of early childhood is as a tool to help people parents and teachers or educators. Provide motivation and stimulate children to carry out various activities in order to find new experiences, Clarify the subject matter given to children, Provide fun for children in playing (learning). This game observation is also designed to train concentration , train motor skills, recognize the concept of cause and effect, train language and insight, recognize colors and shapes. Keywords: Educational games, child develompment